2018
DOI: 10.1017/s0954579418000548
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal programming of postnatal plasticity revisited—And extended

Abstract: Two sets of evidence reviewed herein, one indicating that prenatal stress is associated with elevated behavioral and physiological dysregulation and the other that such phenotypic functioning is itself associated with heightened susceptibility to positive and negative environmental influences postnatally, raises the intriguing hypothesis first advanced by Pluess and Belsky (2011) that prenatal stress fosters, promotes, or “programs” postnatal developmental plasticity. Here we review further evidence consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 173 publications
(232 reference statements)
3
36
0
Order By: Relevance
“…Further, to gain a better understanding which neurobiological mechanisms underlie increased environmental susceptibility in individuals born with larger brain volumes in terms of normal and pathological development, controlled experimental studies in animal models aiming at manipulating neurodevelopmental processes that will affect neonatal brain size are warranted. Interestingly, it has been proposed that the prenatal environment may program postnatal susceptibility to environmental conditions including parenting ( Beijers et al, 2020 ; Hartman and Belsky, 2018 ), with stress-sensitive neurotrophic factors during fetal brain development potentially playing a role ( Hellström et al, 2016 ). We have previously reported that maternal childhood maltreatment was associated with smaller neonatal brain size ( Moog et al, 2018 ), a phenotype that we here observed to underlie lower sensitivity to parenting quality.…”
Section: Discussionmentioning
confidence: 99%
“…Further, to gain a better understanding which neurobiological mechanisms underlie increased environmental susceptibility in individuals born with larger brain volumes in terms of normal and pathological development, controlled experimental studies in animal models aiming at manipulating neurodevelopmental processes that will affect neonatal brain size are warranted. Interestingly, it has been proposed that the prenatal environment may program postnatal susceptibility to environmental conditions including parenting ( Beijers et al, 2020 ; Hartman and Belsky, 2018 ), with stress-sensitive neurotrophic factors during fetal brain development potentially playing a role ( Hellström et al, 2016 ). We have previously reported that maternal childhood maltreatment was associated with smaller neonatal brain size ( Moog et al, 2018 ), a phenotype that we here observed to underlie lower sensitivity to parenting quality.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of individual differences in susceptibility is considered genetic [74] or set in the early, including prenatal, environment. [52,[75][76][77] The DSE is the theory that comes closest to our model. In fact, DSE could be viewed as one particular instance of the variabilityrisk model.…”
Section: Similar Modelsmentioning
confidence: 99%
“…In line with the DSE theory, preliminary data suggest that prenatal stress is associated with markers of increased plasticity of cognitive and/or psychological traits in children. [76] In D. melanogaster, changes in temperature modify the degree of variability in the developmental response (wing size and shape) to genetic factors. [79] Other studies suggest that environmental factors like temperature, pollution, and urbanicity in animals [87][88][89] enhance developmental instability, i.e., variability in response to stochastic factors.…”
Section: Wwwbioessays-journalcommentioning
confidence: 99%
“…Early stages of embryonic development are characterized by heightened brain plasticity that is adversely affected by exposure to environmental insults (13). Complex gene environment interactions during critical early developmental periods may have lasting effects and result in adult psychopathology (14, 15). Maternal stress exposure, anxiety, and depression during pregnancy are considered in utero adverse experiences and have been associated with low birth weight (LBW) and future health problems (1624).…”
Section: In Utero Stress Exposuresmentioning
confidence: 99%